NAVIGATING ACADEMIC PATHWAYS: EXPLORING THE DETERMINANTS OF COURSE CHOICES BY WOMEN STUDENTS – AN INSTITUTION BASED CASE STUDY - Dr. P. Devi Priya,; Dr. M. Helen Mary Jacqueline, (IJRDO - Journal of Business Management, 2025)
Higher education is a sustainable investment of human capital. Choice-based credit system in higher education enables the students to select portfolio of courses as per their interest. The flexible curricular structures and an interdisciplinary approach opens up opportunities for lifelong learning. The study attempts to answer research question the factors influencing the choice of the elective courses among students and their choice behaviour. The first women's college in Madurai district, Tamil Nadu, South India was considered for the study. The final year 290 postgraduates (83 percent) and 1122 undergraduates (81percent) were the student respondents. Factor analysis was used to find the prominent factors determining the choice of electives among the students at both the undergraduate and postgraduate levels. The perspectives varied as per the level of education. The nature of the course, academic and financial lightness, role of peers, academic motivation and diverse interest were the key influencing variables in elective course choice among the postgraduate students. While among the undergraduate’s course package, role of peers and family, academic motivation and nature of the course were the determining factors in elective choice